1992
DOI: 10.1016/0014-5793(92)80654-y
|View full text |Cite
|
Sign up to set email alerts
|

A molecular model for the tumour‐associated antigen, p97, suggests a Zn‐binding function

Abstract: The primary structure of p97 (mclanotransfcrrin) has been compared with other members of the transf'errin superfamily. A molecular structure of p97 has been modellcd based on the crystal structure of diferric rabbit serum transfcrrin. The most significant amino acid substitutions in p97 are almost exclusively limited to only two regions; the C-lobe iron-binding cleft and the intcrlok contact region. The latter includes witbin the N-terminal lobe a &-binding consensus sequence found in metallopeptidases, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has also been noted by some researchers that the Tf-independent Fe uptake pathway is inhibited by a number of transition metals (Wright et al, 1986;Morgan, 1988;Kaplan et al, 1991;Seligman et al, 1991;Olakanmi et al, 1994). Furthermore, based on a molecular model of p97, it appears that p97 has zinc binding properties (Garratt and Jhoti, 1992). This raises the question of whether the Tf-independent or p97-mediated Fe uptake pathway actually provides an alternate pathway for other metals to enter the cell non-competitively with Fe, which would enter the cell via the RME pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted by some researchers that the Tf-independent Fe uptake pathway is inhibited by a number of transition metals (Wright et al, 1986;Morgan, 1988;Kaplan et al, 1991;Seligman et al, 1991;Olakanmi et al, 1994). Furthermore, based on a molecular model of p97, it appears that p97 has zinc binding properties (Garratt and Jhoti, 1992). This raises the question of whether the Tf-independent or p97-mediated Fe uptake pathway actually provides an alternate pathway for other metals to enter the cell non-competitively with Fe, which would enter the cell via the RME pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant molecular modelling studies have demonstrated that a potential Zn(II)‐binding thermolysin consensus sequence in MTf is oriented in an appropriate stereochemical arrangement to allow it to bind Zn(II) that is crucial for metalloprotease activity [44]. Indeed, the Zn‐binding site responsible for catalytic activity in thermolysin is nearly superimposable on the MTf site [44]. Examining the MTf molecules found in a variety of species, only human MTf contains the consensus sequence HE XX H found in metallopeptidases such as thermolysin (Table 2).…”
Section: Possible Functional Roles Of Melanotransferrinmentioning
confidence: 99%
“…In fact, while no significant Zn(II)‐citrate‐transporting role of MTf was identified in our studies (Fig. 4), it has been suggested that the potential Zn(II)‐binding thermolysin consensus sequence in MTf may impart it with metalloprotease activity [46]. Considering our results, further studies have been initiated to examine the metalloprotease activity of MTf and to develop MTf knockout mice, both of which may provide clues to its biological role(s).…”
Section: Discussionmentioning
confidence: 63%